Evaluate the Rutting Performance of Sustainable Gap-Graded Asphalt Mixes Subjected to Moisture Conditioning - Elkut, Foad Mohamed; Hamzah, Meor Othman (Sharwes Scientific Journal, 2025)
Rutting is one of the common pavement distresses which led to lower riding comfort for road users and high maintenance costs. The aim of this study is to enhance the properties of Gap-Graded Asphalt Mixes (GGAM) by using Calcium Carbonate (CaCo3) with new by-product material Treated Palm Oil Fuel Ash (TPOFA) used as a filler. The dynamic modulus (E*) Simple Performance test (SPT) was conducted at 4°C, 21°C, and 37.8°C, and used 10 Hz and 0.5 Hz loading frequencies. The same samples were used for the flow number test (FN) at 54. 4°C to evaluate the Rutting Performance of GGAM subjected to acceleration moisture conditioning using a continuous haversine loading. Results from the study indicated that the SPT test was effective and that enhancement in the stiffness and water sensitivity resistance is achieved by adding CaCO3 with TPOFA to the GGAM. Furthermore, to use new by-product material treated palm oil fuel ash in road pavement wherever available to solve the solid waste disposal problem of the environment.